2021
DOI: 10.1371/journal.pone.0251882
|View full text |Cite
|
Sign up to set email alerts
|

Picturing donations: Do images influence conservation fundraising?

Abstract: Many environmental organizations use photographic images to engage donors and supporters. While images play a role in fundraising, visual framing remains understudied in the environmental field. Few real-world experiments have examined which types of images result in higher donations to biodiversity conservation. We examined the role of images in conservation fundraising through a public experiment at Zoomarine, a marine park located in southern Portugal. Zoomarine runs a program called Dolphin Emotions where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Other studies that have tested different images paired with donation boxes have also found no effect. An experiment at a marine park in Portugal found no effect on donations when a donation box was paired with posters featuring different images (e.g., images of a flagship species, of other animals, of children, or of watching eyes; Salazar et al, 2021). Veríssimo et al (2018) tested whether pairing images of different conservation flagship species with a donation box at Australian Geographic Society shops made a difference in donation amount and found that only the body mass of the animal pictured had a small influence on donation amount.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that have tested different images paired with donation boxes have also found no effect. An experiment at a marine park in Portugal found no effect on donations when a donation box was paired with posters featuring different images (e.g., images of a flagship species, of other animals, of children, or of watching eyes; Salazar et al, 2021). Veríssimo et al (2018) tested whether pairing images of different conservation flagship species with a donation box at Australian Geographic Society shops made a difference in donation amount and found that only the body mass of the animal pictured had a small influence on donation amount.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few realworld experiments focused on conservation fundraising. Offline, Salazar et al (2021) examined the impacts of photographic images on donation behavior at a marine park in Portugal and found no significant difference between four images: dolphins, ocean wildlife, children and watching eyes, while a field experiment at a Japanese mountain park by Kubo et al (2018) found that announcing the information on seed money was superior to sharing the amount of others' contribution to raise funds for the trail maintenance. Looking at online donations, Shreedhar (2021) found Facebook advertisement videos about wild dogs elicited higher traffic than those about elephants.…”
Section: Behavioral Evidence Concerning Donation Behaviormentioning
confidence: 99%
“…Offline, Salazar et al. (2021) examined the impacts of photographic images on donation behavior at a marine park in Portugal and found no significant difference between four images: dolphins, ocean wildlife, children and watching eyes, while a field experiment at a Japanese mountain park by Kubo et al. (2018) found that announcing the information on seed money was superior to sharing the amount of others’ contribution to raise funds for the trail maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the importance of the context in conservation practices, only a few real-world field experiments have been carried out. In terms of offline settings, for example, Salazar et al (2021) examined the impacts of photographic images on donation behavior at a marine park in Portugal and found no significant difference between four images: dolphins, ocean wildlife, children and watching eyes. Kubo et al (2018) carried out at a mountain park in Japan and explored the effects of announcing the information on donation behavior for the trail maintenance.…”
Section: Behavioral Evidence Concerning Donation Behaviormentioning
confidence: 99%